2008
DOI: 10.1002/jclp.20494
|View full text |Cite
|
Sign up to set email alerts
|

The use of symptom severity measured just before termination to predict child treatment dropout

Abstract: The current study examined indices of trauma-related symptom severity as predictors of dropout from exposure-based cognitive behavioral therapy in a sample of 99 child and adolescent trauma victims. The investigation incorporated measures of symptom severity at two time points: pretreatment and just before termination. The results indicated that a model with symptom severity measured just before termination was significantly associated with the number of attended sessions; however, a model with the symptom-sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 32 publications
3
40
1
Order By: Relevance
“…Chasson et al 482 point out that treatment is not static and neither is symptom severity (and possibly other factors that influence engagement). In their study, 482 which explored the predictive value for dropout (from exposure-based CBT) of trauma-related symptom severity, they found that baseline symptom severity failed to predict dropout.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Chasson et al 482 point out that treatment is not static and neither is symptom severity (and possibly other factors that influence engagement). In their study, 482 which explored the predictive value for dropout (from exposure-based CBT) of trauma-related symptom severity, they found that baseline symptom severity failed to predict dropout.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 73 included acceptability studies, the majority were set in the USA (42 studies 107,108,161,175,176,482,492,504,505,510,515,526,533,621, ). The remainder were in Canada (four studies 170,[658][659][660][661] ), the UK (14 studies 145,169,481,511,538,[662][663][664][665][666][667][668][669][670] ) and elsewhere in Europe: the Netherlands (three studies 497,671,672 ), Norway (three studies [673][674][675] ) and Sweden (one study 676 ), with one multisite review of services 145,146,640,[665][666][667][668][669]…”
Section: Description Of Included Acceptability Studiesmentioning
confidence: 99%
See 3 more Smart Citations